Temporal change in dissertation macrostructures. (October 2021) - Anderson, Tim; Okuda, Tomoyo
Abstract: This paper builds on our recent work (Anderson et al., 2020; Anderson & Okuda, 2019 ; Anderson et al., 2021) investigating macrostructural variation in doctoral dissertations. Two of the central questions that remained under-addressed in this (and other) prior research were if and how dissertation macrostructures have changed over time, and what this change might indicate in terms of acceptable and preferred dissertation writing practices and the personal choices and institutional forces that shape dissertation genres. To address this, our present study includes a corpus of 1, 254 doctoral dissertations from a single Canadian research university spanning a 52-year period from 1966 to 2018. As a related question, we were also curious about the proclivity of co-authorship practices in dissertation texts, since previous research (Anderson et al., 2021 ) has demonstrated that co-authorship is common with certain dissertation macrostructures but much less so (or even non-existent) in others. As shown below, both macrostructures and co-authorship demonstrated changes over time in the corpus of texts analyzed for this study. Dissertations are now increasingly manuscript-based and/or contain published sections, many of these co-authored. The authors conclude with implications of this change and calls for further inquiry in this area. Highlights: We analyzed 1254 doctoral dissertations for macrostructure and authorship practices. 52 years of education dissertations were analyzed from one research university. Both macrostructure and (co)authorship practices have changed over time. "Alternative" dissertation macrostructures are now as popular as traditional ones. Co-authorship is common in some macrostructures and non-existent in others.